Knowledge, Attitude, and Practices Toward Tuberculosis Among Hospital Outpatients in Kabul, Afghanistan - Essar, Mohammad Yasir; Rezayee, Khalid Jan; Ahmad, Shoaib; Kamal, Manar Ahmed; Nasery, Reshaduddin; Danishmand, Tamim Jan; Head, Michael; Nemat, Arash (Frontiers in Public Health, 2022)
Background: Tuberculosis (TB) is a high-burden respiratory infectious disease. There was a sharp decline in the number of confirmed TB cases during the pandemic; this is likely to be influenced by the COVID-19 pandemic response, with under-reporting due to resource diversion. There are typically 13000 tuberculosis-associated deaths in Afghanistan annually, with significant problems posed by drug-resistant TB. Method: A cross-sectional descriptive study was conducted in Afghanistan on Kabul residents who visited the adult outpatient departments of public hospitals for any health-related reason from 1st January to 20th March 2022. The study scored their knowledge, attitude, and practices (KAP) towards tuberculosis. Results: Of 829 participants, 450 (54.3%) were males and 379 (45.7) females. The median age was 28 years, and 63.3% were married. The majority of participants were unemployed (75.5%), but 54% had a monthly income greater than 3000 Afghanis, indicating the reliance on family. By TB knowledge score, 727(87.7%) participants had good TB knowledge, and 800 (96.5%) participants had a positive attitude towards TB treatment and control. Only 2 participants reported poor practices regarding TB prevention. Conclusion: The study findings highlighted that outpatients in Kabul had good knowledge, attitude, and practice toward TB. More studies are needed to highlight KAP in different Afghan populations, including in other parts of the country.